You are safe here: a flyer with re-orientating messages for families of patients with delirium in the intensive care unit: brief report - Nydahl, Peter; Chahdi, Mohamed; Debue, Anne-Sophie; Deffner, Teresa; Galazzi, Alessandro; Gallie, Louise; La-Calle, Gabriel Heras; Krotsetis, Susanne; Lewko, Agnieszka; Lindroth, Heidi; Liu, Keibun; Paulino, Maria Carolina; et al. (Nursing in critical care, 2024)
Patients in delirium require trustful communication and re-orientation. We developed a flyer with positive, re-orientating suggestions for families of delirious patients in intensive care units. Suggestions include creating a safe environment, interpreting unusual behaviours positively and fostering mental resilience. Additionally, families are encouraged to prioritize their own well-being, recognizing their crucial role in supporting their loved ones. This flyer offers practical strategies across four key areas: ensuring security and orientation, reframing noises and body experiences, managing agitation and reshaping perceptions. By equipping families with knowledge and tools, this resource aims to promote understanding, resilience and strength to humanize delirium care.
Erstmals veröffentlicht: 03. Oktober 2024
Gesehen am 07.01.2025